Answer:
Step-by-step explanation:
Answer:
y=1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
6=2(y+2)
6=(2)(y)+(2)(2)(Distribute)
6=2y+4
Step 2: Flip the equation.
2y+4=6
Step 3: Subtract 4 from both sides.
2y+4−4=6−4
2y=2
Step 4: Divide both sides by 2.
2y/2 2/2
b. 56 − 72 = x
c. 56 + x = 72
d. 56 + 72 = x
Answer:
C. 56 + x =72
Answer:The equivalent ratio of 6:3 is 2:1. To find the equivalent ratio, we divide both terms of the original ratio by the greatest common divisor (GCD) of the two terms.
In this case, the GCD of 6 and 3 is 3. So, we divide both terms by 3:
6 ÷ 3 = 2
3 ÷ 3 = 1
Therefore, the equivalent ratio of 6:3 is 2:1. This means that for every 2 parts of the first quantity, there is 1 part of the second quantity.
For example, if we have 6 apples and we want to find the equivalent number of oranges, we can use the ratio 2:1. So, if we have 6 apples, we would have 3 oranges (since 2 parts of apples is equal to 1 part of oranges).
Remember, when finding equivalent ratios, it is important to divide both terms by the same number to maintain the same ratio relationship.
Tax rate is 6%, price is 1000 off the sticker price, $p.